Automatic light curve processing for exoplanet identification using machine learning algorithms (Revista Brasileira de Iniciação Científica, 2024)
approaches based on machine learning techniques have been proposed in the literature to assist in the detection of exoplanets through automated processing of light curves. Despite advancements, traditional machine learning algorithms have not yet been fully studied for this task. Therefore, in this work, we proposed the definition of a baseline through an extensive experimental evaluation involving 16 algorithms with different parameter settings. To achieve this goal, in this study, data from the Kepler telescope was used, totaling 5302 light curves, each with 60000 records. As the main result of the experimental evaluation, the LightGBM algorithm showed the best performance, with an accuracy rate of 82.92%.
Keywords: astronomy. exoplanet. machine learning. light curve.